We Still Have a Dream. A Plea for a Sensibly Audacious Science - Marlies De Munck; Pascal Gielen (Антиномии, 2022)
Today, academic research in the human and social sciences is dominated by analytical, objectivistic methods that push an aesthetic understanding and interpretation of the world beyond the ranks of science. This not only deprives the modern project of a humanistic kind of knowledge. The individualistic career model that is sanctified by the contemporary scientific ideal of detachment also thwarts the collective modern dream of progress. However, this article argues that aesthetic thinking and dreaming of a better future are substantial parts of the original modern project, as we see in the early modern thinking of Descartes and Bacon. This article wants to revalue aesthesis as an essential part of knowledge and pleas, in line with Nietzsche, for a sensibly audacious science.